2019
DOI: 10.1177/000313481908500433
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a More Restrictive Transfusion Trigger in Trauma Patients

Abstract: Since the Transfusion Requirements in Critical Care trial, studies have shown that acutely ill patients can drift as a low as 5 g/dL. This study reviews a transfusion trigger change to 6.5 g/dL, which we hypothesize will conserve resources and improve quality of care. This is a retrospective chart review at an urban Level I trauma center from January through December 2015 after our trauma service changed the transfusion trigger from 7 to 6.5 g/dL. Outcomes in patients before (TT7) and after (TT6.5) the change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…However, high-quality data were only available in cardiac, orthopaedic surgery and critical care patients and no study on acute bleeding in trauma patients was included in the analysis. In a small-sample-size before–after study ( n = 131 patients) in which the transfusion threshold was decreased from 70 to 65 g/L in a trauma centre, no difference was reported in hospital length of stay or organ failure [ 178 ]. Above all, physicians should keep in mind that haemorrhagic shock may be a rapidly evolving situation in which anticipation of transfusion is essential to prevent an excessive decrease in arterial oxygen transport and the decision to transfuse should not be based on haemoglobin levels alone.…”
Section: Resultsmentioning
confidence: 99%
“…However, high-quality data were only available in cardiac, orthopaedic surgery and critical care patients and no study on acute bleeding in trauma patients was included in the analysis. In a small-sample-size before–after study ( n = 131 patients) in which the transfusion threshold was decreased from 70 to 65 g/L in a trauma centre, no difference was reported in hospital length of stay or organ failure [ 178 ]. Above all, physicians should keep in mind that haemorrhagic shock may be a rapidly evolving situation in which anticipation of transfusion is essential to prevent an excessive decrease in arterial oxygen transport and the decision to transfuse should not be based on haemoglobin levels alone.…”
Section: Resultsmentioning
confidence: 99%
“…5,11,[20][21][22] In addition to conserving inventory, reducing unnecessary transfusions also reduces associated risks and complications. 5,11,17,23 The 2016 Clinical Practice Guidelines from the AABB recommend a pre-transfusion hemoglobin threshold of 7-8 g/dL in most hemodynamically stable adult patients. 24 Lowering the pre-transfusion hemoglobin threshold from 7.0 to 6.5 g/dL or lower in stable, asymptomatic patients, while outside of evidence-based practice, has been proposed as one strategy to conserve RBCs during long-term severe blood supply shortages.…”
Section: Introductionmentioning
confidence: 99%
“…4 Garland-Kledzik et al showed that reducing the pre-transfusion hemoglobin threshold from 7.0 to 6.5 g/dL in trauma patients was not associated with increased morbidity or mortality but was associated with decreased RBC utilization. 23 At an academic medical center the existing BPA for inpatient locations that previously alerted providers when an order for RBC transfusion was placed on a patient with a pre-transfusion hemoglobin greater than 7.0 g/dL 11 was modified to activate at pre-transfusion hemoglobin greater than 6.5 g/dL. This change was implemented on June 1, 2021 after notification from the medical center's blood supplier of an impending critical RBC shortage, initially expected to last at least through the summer months, that was subsequently extended until 3/1/2022.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations